2014
DOI: 10.1155/2014/763934
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Particulate Matter Air Pollution in Mpererwe District, Kampala, Uganda: A Pilot Study

Abstract: Air quality in Kampala, the capital of Uganda, has deteriorated significantly in the past two decades. We made spot measurements in Mpererwe district for airborne particulate matter PM2.5 (fine particles) and coarse particles. PM was collected on Teflon-membrane filters and analyzed for mass, 51 elements, 3 anions, and 5 cations. Both fine and coarse particle concentrations were above 100 µg/m3 in all the samples collected. Markers for crustal/soil (e.g., Si and Al) were the most abundant in the PM2.5 fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 10 publications
2
34
0
Order By: Relevance
“…All analyses were conducted at the Desert Research Institute (Reno, NV). According to the mass construction approach used previously (23), the major components that accounted for 83% of the mass of PM 2.5 consisted of 4.5% sulfate, 2.1% nitrate, 30.9% carbon, and 46.2% crustal elements. Similarly, the major components accounting for 75% of the mass of PM 10 consisted of 5.6% sulfate, 1.8% nitrate, 29.0% carbon, and 39.4% crustal elements.…”
Section: Resultsmentioning
confidence: 99%
“…All analyses were conducted at the Desert Research Institute (Reno, NV). According to the mass construction approach used previously (23), the major components that accounted for 83% of the mass of PM 2.5 consisted of 4.5% sulfate, 2.1% nitrate, 30.9% carbon, and 46.2% crustal elements. Similarly, the major components accounting for 75% of the mass of PM 10 consisted of 5.6% sulfate, 1.8% nitrate, 29.0% carbon, and 39.4% crustal elements.…”
Section: Resultsmentioning
confidence: 99%
“…Although direct measurement of PM 2.5 is more labor‐intensive, some studies have shown that carbon monoxide does not serve as a reliable proxy for PM 2.5 levels . Finally, while other studies from Uganda have focused on ambient air pollution in urban locations, the issue of indoor air pollution from combustion sources is likely more relevant to most populations in low‐ and middle‐income countries, who live predominantly in rural areas…”
Section: Discussionmentioning
confidence: 99%
“…The spatial heterogeneity of air pollution and the lack of detailed, long‐term air quality studies make it difficult to quantify trends, but air pollution in Kampala is generally understood to be worsening. Previous reports have measured average outdoor PM 2.5 concentrations between 104 and 132 μg/m 3 , highlighting the need for more continuous monitoring of ambient PM 2.5 concentrations in this African city and others …”
Section: Discussionmentioning
confidence: 65%